(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In the article the place XVII century economic history of Europe. Analyzes the work of scientists who have studied the issue, showing the extent of its coverage. The approach to solving the neglected issues. It provides an opportunity to study the economic history of Europe with its own characteristics, specific phenomena and processes. It is established that in the XVII century in the lands east of the Elbe river behind the economic development of Western countries. The main reason – the great feudal strengthening industrial – agricultural estates, which were based on non-economic coercion and brutal feudal exploitation. The new economic system of production called «second edition of serfdom». Eastern Europe is food and raw materials appendage to the developed Western European countries. XVII century economic history of Europe is the boundary between two economic systems of production – feudal and market, between the two world – historical landmarks – the Middle Ages and new time. XVII century initiated the establishment industrыalnoyi civilization.